2002
DOI: 10.1111/j.1748-5827.2002.tb00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of aldosterone in hypertension associated with spontaneous pituitary‐dependent hyperadrenocorticism in dogs

Abstract: The aim of this study was to evaluate the role of aldosterone as an initiating and/or perpetuating factor in hypertension associated with pituitary-dependent hyperadrenocorticism (PDH) in dogs. Thirteen dogs with PDH and 11 healthy control dogs were used. In all dogs, arterial blood pressure and plasma sodium, potassium, basal aldosterone, post-ACTH aldosterone, basal cortisol and post-ACTH cortisol concentrations were measured. The tests were repeated 10 days and three months after the beginning of o,p'-DDD t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 10 publications
4
39
1
9
Order By: Relevance
“…Trilostane does appear to reduce ACTH stimulated aldosterone concentrations in dogs with HAC [12,44]. A reduction in both basal and ACTH stimulated aldosterone concentrations is also seen in mitotane treated dogs [42,43]. In all 3 of the trilostane studies the observed effects on aldosterone concentrations were less pronounced than the effects on cortisol concentrations.…”
Section: Aldosteronementioning
confidence: 74%
See 1 more Smart Citation
“…Trilostane does appear to reduce ACTH stimulated aldosterone concentrations in dogs with HAC [12,44]. A reduction in both basal and ACTH stimulated aldosterone concentrations is also seen in mitotane treated dogs [42,43]. In all 3 of the trilostane studies the observed effects on aldosterone concentrations were less pronounced than the effects on cortisol concentrations.…”
Section: Aldosteronementioning
confidence: 74%
“…Aldosterone secretion in dogs with untreated HAC is generally considered to be decreased [42,43]. The effect of trilostane on aldosterone in dogs with HAC has been reported in 3 studies.…”
Section: Aldosteronementioning
confidence: 99%
“…Segundo Ortega et al (1996) e Goy- Thollot et al (2002), o tempo de duração da hipercor- Fig.2. Representação dos valores da mediana (linha horizontal dentro do quadrilátero), dos percentis de 25% e de 75% (delimitação do quadrilátero) e máximo e mínimo (extremidade das barras verticais) da concentração de albumina normalizada da urina de cães clinicamente normais (Controle), de cães com hiperadrenocorticismo hipertensos (Grupo I) e de cães com hiperadrenocorticismo normotensos (Grupo II).…”
Section: Discussão E Conclusãounclassified
“…A presença concomitante de hipertensão arterial sistêmica e proteinúria nos cães com hiperadrenocorticismo já foram anteriormente relatadas (Ortega et al 1996, Goy--Thollot et al 2002, Boutilier et al 2004, Cavalcante et al 2007, Mazzi et al 2008, no entanto, a intensidade de albuminúria relacionado com a hipertensão arterial sistêmica foi avaliada até o presente momento por testes semiquantitativos (Boutilier et al 2004, Cavalcante al. 2007, Mazzi et al 2008, Lien et al 2010.…”
Section: Discussão E Conclusãounclassified
See 1 more Smart Citation